2022
DOI: 10.1111/meca.12391
|View full text |Cite
|
Sign up to set email alerts
|

Tax evasion and social reputation: The role of influencers in a social network

Abstract: In this paper, we present an agent-based model in which taxpayers 'live' in a network and care about their social reputation. Individuals decide whether to pay or to evade taxes considering the expected economic net benefit and the reputational cost from tax evasion. Individuals differ in income and in the weight they attach to social reputation, which is updated by assessing the opinions shared in their reference group. The reference group contains individuals irrespective of their income (integrated society)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The Social Influence Theory (SIT) is applicable in explaining the relationship between taxpayer perception and tax compliance. Research by Di Gioacchino & Fichera (2022) presented an agent-based model in which taxpayers live in a network and care about their social reputation, where individuals decide whether to pay or to evade taxes considering the expected economic net benefit and the reputational cost from tax evasion. The study found that in a society where people from different income levels mix (integrated society), everyone tends to follow the same behavior, either all paying taxes or all evading them.…”
Section: Social Influence Theorymentioning
confidence: 99%
“…The Social Influence Theory (SIT) is applicable in explaining the relationship between taxpayer perception and tax compliance. Research by Di Gioacchino & Fichera (2022) presented an agent-based model in which taxpayers live in a network and care about their social reputation, where individuals decide whether to pay or to evade taxes considering the expected economic net benefit and the reputational cost from tax evasion. The study found that in a society where people from different income levels mix (integrated society), everyone tends to follow the same behavior, either all paying taxes or all evading them.…”
Section: Social Influence Theorymentioning
confidence: 99%
“…The income in this special segment of taxpayers (influencers) are mostly those that are not declared to the tax system and generate non-compliance with tax obligations. [9] mention that many of the influencers prioritize tax compliance and their tax obligations, making their followers follow the same behavior, because the social norm mentions that their individual tax behavior will depend on the expected net monetary benefit, tha's if tax evasion is going to harm their social reputation, then the influencer will take it very seriously to regularize their income to the tax system. On the other hand according to [10] the cause could be the lack of adequate instructive reports on tax issues towards the taxpayer.…”
mentioning
confidence: 99%